Virtual sports deserve real sports medical attention. Issue 1 (1st December 2019) - Pereira, Ana Monteiro; Brito, João; Figueiredo, Pedro; Verhagen, Evert
Abstract : In recent years, virtual sports or 'eSports' have grown exponentially both recreationally and at the professional level. eSports comprise several regulated video games played competitively, using electronic platforms. Some eSports competitions present a structure comparable to traditional sports, and eSports players, even with major skills and mental focus, need preparation and training to thrive. However, little is known about the demands of eSports competitions and continuous training. As the popularity and stakes rise, concerns about the health and emerging risks of eSports participation might arise. Indeed, in the absence of proper descriptive data about the specific characteristics of the eSports population (including factors such as screen time, physical activity, overuse injuries or training environment), effective prevention and care cannot be developed nor provided. Therefore, quality healthcare and prevention strategies are needed. In the current viewpoint, we argue that those involved with Sports Science and Medicine should lead the discussion and reflect on the health effects of eSports participation, providing scientifically-based arguments to better answer to the current eSports professionalism.